2021
DOI: 10.1101/2021.03.17.435767
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis of GTPase-mediated mitochondrial ribosome biogenesis and recycling

Abstract: Ribosome biogenesis is an essential process that requires auxiliary factors to promote folding and assembly of ribosomal proteins and RNA. In particular, maturation of the peptidyl transferase center (PTC), the catalytic core of the ribosome, is mediated by universally conserved GTPases, but the molecular basis is poorly understood. Here, we define the mechanism of GTPase-driven maturation of the human mitochondrial ribosomal large subunit (mtLSU) using a combination of endogenous complex purification, in vitr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 46 publications
1
7
1
Order By: Relevance
“… States I–VIII along the human mtLSU late-stage maturation pathway, including recently reported states II ( Cheng et al, 2021 ), III ( Brown et al, 2017 ), IV ( Cipullo et al, 2021 ; Hillen et al, 2021 ), V ( Hillen et al, 2021 ), VI (this study), and VIII ( Amunts et al, 2015 ). Note that state V was seen only to contain GTPBP6 and GTPBP7 is therefore depicted hollow.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“… States I–VIII along the human mtLSU late-stage maturation pathway, including recently reported states II ( Cheng et al, 2021 ), III ( Brown et al, 2017 ), IV ( Cipullo et al, 2021 ; Hillen et al, 2021 ), V ( Hillen et al, 2021 ), VI (this study), and VIII ( Amunts et al, 2015 ). Note that state V was seen only to contain GTPBP6 and GTPBP7 is therefore depicted hollow.…”
Section: Discussionsupporting
confidence: 60%
“…The studies, however, differ notably in the precise step during assembly, the biogenesis factors recruited, and finally, the GTPase in control. The deleterious consequences of manipulating NSUN4 or MTERF4 binding to the mitoribosome in vivo illustrate the importance of these proteins in mediating not only the exact step during PTC maturation that we have trapped, but also the prior and subsequent steps described in Cheng et al, 2021 ; Cipullo et al, 2021 ; Hillen et al, 2021 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Analysis of the methylation of 16S mt-rRNA nucleotides in MRM1-3 knock-out models showed that the 2'-O-methylation of U1369 by MRM2 depends on the prior modification of U1370, substrate of MRM3 (Figure 1). This implies that MRM3 exerts its activity over the assembling mtLSU prior to MRM2, adding molecular evidence to support structural findings (Chandrasekaran et al, 2021;Cheng et al, 2021;Hillen et al, 2021;Lenarčič et al, 2021).…”
Section: Discussionmentioning
confidence: 55%
“…The late stages of mtLSU assembly involve almost exclusively the remodelling of interfacial RNA elements of otherwise complete particles, as shown by recent structural studies (Chandrasekaran et al, 2021;Cheng et al, 2021;Hillen et al, 2021;Lenarčič et al, 2021). Key players include the helicase DDX28, which dislocates the central protuberance to increase solvent exposure of the intersubunit interface, the MTERF4:NSUN4 complex, which holds H68-71 of domain IV of 16S mt-rRNA in an immature conformation to allow access of assembly factors to the PTC, and the GTPases GTPBP5, GTPBP6, GTPBP7 and GTPBP10, which coordinate the maturation of the PTC through a series of conformational rearrangements.…”
Section: Discussionmentioning
confidence: 93%